Optimized Oxidative Stress Protocols for Low-microliter Volumes of Mammalian Plasma - Langille, Evan A. (Bio Protoc, 2019)
Small blood volumes commonly obtained from small mammals during field studies are only sufficient for a single biochemical assay. In this study, we used blood collected from a population of wild eastern chipmunks (Tamias striatus) and developed modified methods to improve analytical selectivity and sensitivity required for measuring markers of oxidative stress using small blood volumes. Specifically, we proposed a modified malondialdehyde (MDA) analysis protocol by high performance liquid chromatography (HPLC) and also optimized both the uric acid independent ferric reducing antioxidant power (FRAP) and hypochlorous acid shock capacity (HASC) assays. We present methods in which a total volume of less than 60 μl of plasma is required to obtain a comprehensive portrait of an individual’s oxidative profile.